Allogeneic Human Umbilical Cord Mesenchymal Stem Cells for the Treatment of Autism Spectrum Disorder in Children: Safety Profile and Effect on Cytokine Levels. (11th June 2019) - Riordan, Neil H.; Hincapié, Maria Luisa; Morales, Isabela; Fernández, Giselle; Allen, Nicole; Leu, Cindy; Madrigal, Marialaura; Paz Rodríguez, Jorge; Novarro, Nelson
Abstract: Individuals with autism spectrum disorder (ASD) suffer from developmental disabilities that impact communication, behavior, and social interaction. Immune dysregulation and inflammation have been linked to children with ASD, the latter manifesting in serum levels of macrophage-derived chemokine (MDC) and thymus, and activation-regulated chemokine (TARC). Mesenchymal stem cells derived from umbilical cord tissue (UC-MSCs) have immune-modulatory and anti-inflammatory properties, and have been safely used to treat a variety of conditions. This study investigated the safety and efficacy of UC-MSCs administered to children diagnosed with ASD. Efficacy was evaluated with the Autism Treatment Evaluation Checklist (ATEC) and the Childhood Autism Rating Scale (CARS), and with measurements of MDC and TARC serum levels. Twenty subjects received a dose of 36 million intravenous UC-MSCs every 12 weeks (four times over a 9-month period), and were followed up at 3 and 12 months after treatment completion. Adverse events related to treatment were mild or moderate and short in duration. The CARS and ATEC scores of eight subjects decreased over the course of treatment, placing them in a lower ASD symptom category when compared with baseline. MDC and TARC inflammatory cytokine levels also decreased for five of these eight subjects. The mean MDC, TARC, ATEC, and CARS values attained their lowest levels 3 months after the last administration. UC-MSC administration in children with ASD was therefore determined to be safe. Although some signals of efficacy were observed in a small group of children, possible links between inflammation levels and ASD symptoms should be further investigated. Stem Cells Translational Medicine   2019;8:1008–1016 : Abstract : A phase I/II study of repeated doses of intravenous allogeneic human umbilical cord mesenchymal stem cell infusions for the treatment of autism spectrum disorder in children (20 subjects). Participants were treated safely with no treatment-related serious adverse events. Some signals of efficacy, notably in serum levels of macrophage-derived chemokine and thymus and activation-regulated chemokine, were observed in some subjects.